Nitrite removal with potential value-added ingredients accumulation via Chlorella sp. L38. (October 2020) - Li, Shuhong; Zheng, Xuechao; Chen, Ye; Song, Chunfeng; Lei, Zhongfang; Zhang, Zhenya
Graphical abstract: Highlights: Biological nitrite removal potential via Chlorella sp. L38 was investigated and intensified. Nitrite removal rate in the Chlorella sp. L38 cultivation process could achieve 57.1 μmol/L/d. The potential value-added ingredients production associated with nitrite removal was also tested. The polysaccharides, lipid and protein productivity could achieve 4.8 mg/g/d, 3.0 mg/L/d and 5.5 mg/L/d. Abstract: Nitrite removal is necessary and significant for pickle and meat processing wastewater. In this study, Chlorella sp. L38 is used as an alternative to remove nitrite and reuse it as nitrogen source for potential value-added ingredients production. Based on the typical BG11 medium with and without NaNO3 (which is the conventional nitrogen source), nitrite is additionally provided, and its concentration gradient was set at 0, 50, 100, 150 and 200 μmol/L, respectively. The experimental results showed that the nitrite removal rate could achieve 57.1 μmol/L/d. In addition, the biomass variation, and value-added ingredients (polysaccharides, lipid, and protein) productivity were also measured, and their yield could achieve 4.8 mg/g/d, 3.0 mg/L/d and 5.5 mg/L/d, respectively. It indicated that Chlorella sp . L38 has the potential to be an environmentally friendly approach for nitrite removal of wastewater.